Pola Asuh Anak Perempuan Pada Keluarga Imran: Telaah Q.S Ali Imran Ayat 35-37 - Iskandar, Riki; Munadi, Muhammad (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
The purpose of this study is to identify the background of Imran's wife vowing to give up her son to serve in Baitul Maqdis; describe the reaction of Imran's wife after learning that the child she gave birth to was a girl; find out the reason Imran's wife entrusted the care of Maryam to Zakaria as. This research is a library research. Primary data sources in this study are Q.S Ali Imran verses 35-37 which are reviewed from Tafsir Al-Mishbah, Tafsir Ibn Katsir, Hurlock's Child Development book, and Santrock's Children book. While secondary data sources are obtained from other literature related to parenting girls. The data collection technique used is documentation. Data validity in this research is contingency technique. Furthermore, the technique used in analyzing this data is content analysis. The results showed that: 1) The parenting of girls in Imran's family can be observed from the efforts to fulfill the vow of Imran's wife who gave up her son to serve in Baitul Maqdis. In the perspective of psychology, Q.S Ali Imran [3]:35 describes the prenatal period. The parenting pattern that Hannah applied at that time, namely authoritarian parenting. 2) Then Q.S Ali Imran [3]:36 expresses the disappointment of Imran's wife for giving birth to a girl, trying to accept and give the best name for her child, and asking Allah Swt. so that the child and his descendants are protected from the temptation of the accursed devil. In general, this verse discusses the post-natal period. It is during this period that Hannah applies democratic parenting characterized by giving good names and praying for goodness to child. 3) Maryam was raised and educated under the care of Zakaria as by applying democratic parenting, which is supported by dialogue and supervision as stated in Q.S Ali Imran [3]:37.